2014
DOI: 10.1111/ijpp.12165
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of a multi-site community pharmacy–based chronic obstructive pulmonary disease support service

Abstract: Objectives Chronic obstructive pulmonary disease (COPD) is a progressive chronic condition that can be effectively managed by smoking-cessation, optimising prescribed therapy and providing treatment to prevent chest infections from causing hospitalisation. The government agenda in the UK is for community pharmacists to become involved in chronic disease management, and COPD is one area where they are ideally located to provide a comprehensive service.This study aims to evaluate the effect of a community pharma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
77
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(88 citation statements)
references
References 25 publications
6
77
0
3
Order By: Relevance
“…This is consistent with other studies which show that pharmacist-delivered interventions can lead to significant improvement in medications adherence in other diseases [30,31]. Two studies [23,25,26] in this review showed that the provided interventions were cost-effective in terms of reducing hospitalisation rate and severe exacerbation rate. There was a cost saving of £94.12 per patient (equivalent to €133) for six months in Wright et al [23] study in the UK and €227 per patient for one year in Tommelein et al [25,26] study in Belgium.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This is consistent with other studies which show that pharmacist-delivered interventions can lead to significant improvement in medications adherence in other diseases [30,31]. Two studies [23,25,26] in this review showed that the provided interventions were cost-effective in terms of reducing hospitalisation rate and severe exacerbation rate. There was a cost saving of £94.12 per patient (equivalent to €133) for six months in Wright et al [23] study in the UK and €227 per patient for one year in Tommelein et al [25,26] study in Belgium.…”
Section: Discussionsupporting
confidence: 91%
“…With respect to IT, the offered interventions were found to significantly reduce IT errors or even improve the choice of the inhaler [5, 23-25, 28, 29]. For MA, the review showed that CPs interventions resulted in improving adherence to inhaled medications which was statistically significant in the addressed studies [8,23,25]. This is consistent with other studies which show that pharmacist-delivered interventions can lead to significant improvement in medications adherence in other diseases [30,31].…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…It has been shown that pharmaceutical care of patients with obstructive respiratory diseases improves medication adherence [24][25][26][27] and achieves a better use of inhalers [26,[28][29][30] and control of the disease [31,32]. In a randomized controlled study to investigate the effect of a simple educational intervention concerning DPI technique delivered by community pharmacists to patients with asthma, a simple educational intervention taking only 2.5 min and targeting inhaler technique was feasible for delivery by community pharmacists and resulted in improved clinical and humanistic outcomes for patients with asthma [33].…”
Section: Discussionmentioning
confidence: 99%